Towards reducing flood risk disasters in a tropical urban basin by the development of flood alert web application. (May 2022) - Mattos, Tiago Souza; Oliveira, Paulo Tarso S.; Bruno, Leonardo de Souza; Carvalho, Glauber Altrão; Pereira, Rodrigo Bahia; Crivellaro, Leonardo Lazarino; Lucas, Murilo Cesar; Roy, Tirthankar
Abstract: We developed a Decision Support System (DSS) coupled with a flood alert web application and evaluated in the Prosa Basin (Midwestern Brazil) to send early flood warning messages to ordinary people. The Hydrologic Engineering Center's Hydrologic Modeling System (HEC-HMS) and River Analysis System (HEC-RAS) were used as the core of flood alert system. As an input of the calibrated HEC-HMS model, we used the Quantitative Precipitation Forecast (QPF) of Weather Research and Forecasting (WRF). The application based on Progressive Web Application (PWA) was developed to support the visualization of flood forecasted and to deliver early warning messages for mobile devices. Our findings show the proposed flood alert system is able to simulated flood events using QPF of WRF and with a 48 h lead time. The DSS developed here is an important information to decision making by the public authorities as well as to ordinary people for reducing flood disasters. Highlights: A Decision Support System (DSS) coupled with a flood alert web application was developed. The DSS is able to simulated flood events with a 48 h lead time. Our findings have a great potential for saving financial costs and reducing human losses.